Measuring the Efficiency of Contiform Machines with the Overall Equipment Effectiveness Method at PT Tirta Investama Pandaan - Okistyawan, Beny; Asyari, Subchan (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
PT Tirta Investama Pandaan Plant is a manufacturing company focused on mineral drinking water (Bottled Water) production. So as to produce a standards product need to take the role of the machine to help people to do it, in the production process machine performance is still not effectively and efficiently yet, so that need for machines maintenance and performance measurement. One method used to measure the effectiveness of that Overall Equipment Effectiveness (OEE). The principles contained in this method are Avaibility, Performance and Quality. From the results of research conducted Contiform machine OEE values obtained 75.62%. Therefore, according JIMP could not be categorized as a Word Class Company. It is necessary to Six Big Losses calculation that includes Equipment Failure Set up and Adjustment Losses, Idle Stopppage Minor Losses, Reduce Speed Defect and Rework Quality and Yield or Losses. Six Big Losses From calculations carried out, there are 2 types of losses are dominant, namely Idle Minor Stopage with a percentage of the value of the Reduce Speed 13:53% and amounted to 29.82%. So do need root cause analysis that includes human factors, machine, material and method with fishbone diagram.